Seagrasses in the Eastern Tropical Pacific: species, distribution, ecology, blue carbon, and threats - Samper Villarreal, Jimena (2024)
Eastern Tropical Pacific (ETP) seagrasses are composed of three genera and four species: Halophila baillonii, Halodule beaudettei, Halodule wrightii, and Ruppia maritima. These are colonizing seagrass species and meadows in the ETP can be ephemeral. Current seagrass distribution in this region remains unknown, with verified extant presence at a limited number of locations and mapping heavily reliant on historical reports. Suitable environmental conditions for seagrasses in the ETP consist of sheltered bays <10 m depth with fine sediment, 19-35 salinity, 26-32C temperature, and water transparency of up to 10 m Secchi depth. In this region, seagrass organic carbon (OC) biomass pools (<0.2 Mg ha-1) have been reported from three locations, while sediment bulk density (<1.4 g mL-1) and OC (<24 Mg ha-1) have been reported from eight locations, all found on the Pacific coast of Costa Rica. Recent blue carbon reports from the ETP have not been included in global assessments to date. OC sequestration and sediment accumulation rates are currently unknown. Seagrasses provide key ecosystem services yet they are also threatened by anthropogenic and natural stressors. Seagrasses have already disappeared from two locations within the ETP, with restoration efforts currently underway on the northern Pacific coast of Costa Rica. This overview of our current understanding of seagrasses in the ETP and their services highlights the need for further research in this understudied region.